Modified Citrus Pectin as a Potential Sensitizer for Radiotherapy in Prostate Cancer. (December 2018) - Conti, Sefora; Vexler, Akiva; Hagoel, Lior; Kalich-Philosoph, Lital; Corn, Benjamin W.; Honig, Nir; Shtraus, Natan; Meir, Yaron; Ron, Ilan; Eliaz, Isaac; Lev-Ari, Shahar
Background: Radiotherapy is one of the primary therapies for localized prostatic carcinoma. Therefore, there is an emerging need to sensitize prostatic cancer cells to chemotherapy/radiotherapy. Modified citrus pectin (MCP) is an effective inhibitor of galectin-3 (Gal-3), which is correlated with tumor progression, proliferation, angiogenesis, and apoptosis.Purpose: This study was directed to evaluate the efficacy of combining ionizing radiation (IR) with MCP on PCa cells.Study Design: Effects of treatments on PCa cells survival were evaluated using XTT assay, flow cytometry, and clonogenic survival assay. Expression of selected proteins was estimated using western blotting. Cell motility, migration, and invasion were determined. Contribution of reactive oxygen species production to treatment effects on cell viability was tested.Results: Radiotherapy combined with MCP reduced viability and enhanced radiosensitivity associated with a decrease in Gal-3, cleavage of the precursor of caspase-3, increased expression of the pro-apoptotic protein Bax, and downregulation of DNA repair pathways, poly-ADP-ribose polymerase, and proliferating cell nuclear antigen. MCP significantly reduced the invasive and migratory potential of PCa cells. Combining sodium pyruvate with MCP and IR mitigated the effect on cell viability.Conclusion: Our findings demonstrated that MCP sensitized PCa cells to IR by downregulating anti-apoptotic Gal-3, modulating DNA repair pathways, and increasing ROS production. For the first time the correlation between MCP, radiotherapy, and Gal-3 for prostatic cancer treatment was found. In addition, MCP reduced the metastatic properties of PCa cells. These findings provide MCP as a radiosensitizing agent to enhance IR cytotoxicity, overcome radioresistance, and reduce clinical IR dose.